Catastrophic Household Health Expenditures and its Poverty Impact (A Case Study of Rural and Urban Area of Eastern Chitwan) - Giri, Krishna (Interdisciplinary Journal of Management and Social Sciences, 2021)
The principle of "health as a fundamental right of the people" is enshrined in the constitution of Nepal 2072 which has guided the state’s obligation towards good health for all Nepali people. In order to ensure this constitutional obligation there is a need to provide equitable health services that factor in differences in geographical area, gender, caste and economic conditions. The study describes the field study on the catastrophic health expenditure and its impact on poverty in Ratnanagar municipality and shaktikhor village of eastern chitwan. The people in the study area are highly affected by catastrophic health expenditure. Catastrophic health expenditure is experienced by all socio- economic groups but severe impoverishment impact is experienced by poor. The impact of out-of pocket payments for health care can become catastrophic over time and can significantly affect the living standards, welfare and poverty of individuals or household. The study is based on primary as well as secondary data. Primary data were collected from primary sources. The sources of primary data are obviously based on the information obtained from the head of the households. A household survey and group discussion techniques were used to obtain statistical data and required information. The findings reveal that 28 percent of the total studied households are experiencing catastrophic health expenditure. 7 percent of the household are poor and 6 percent of the households fall below the poverty line because of the health expenditure. It was also found that the normalized poverty gap as 1.97 percent whiles the poverty gap after deduction of OOP is 2.65 percent (an increase by 0.68 percent). This indicates a percentage point change by 34.5 percent of the conventional poverty gap.